Multivariate Time Series Analysis of Bank Financial Behavior - Cramer, Robert H.; Miller, Robert B. (Journal of Financial and Quantitative Analysis, 1978)
The bank financial management process involves assets, liabilities, and factors external to the bank and thus is multivariate. Because variables such as deposits, loans, or interest rates are often related with a time lag to another variable such as investments, the process is also dynamic. Although the research work of Aigner [1], Aigner and Bryan [2], Anderson and Burger [3], Bryan [6], Bryan and Carleton [7], Fraser and Rose [10], Hester and Pierce [13], and Melnik [14] has dealt with the multivariate aspect of the process, the consideration of dynamic properties in empirical work has been limited.